2019
DOI: 10.1016/j.bja.2019.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine modulates neuroinflammation and improves outcome via alpha2-adrenergic receptor signaling after rat spinal cord injury

Abstract: Background: Spinal cord injury induces inflammatory responses that include the release of cytokines and the recruitment and activation of macrophages and microglia. Neuroinflammation at the lesion site contributes to secondary tissue injury and permanent locomotor dysfunction. Dexmedetomidine (DEX), a highly selective a2-adrenergic receptor agonist, is anti-inflammatory and neuroprotective in both preclinical and clinical trials. We investigated the effect of DEX on the microglial response, and histological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…dex has a high affinity for α2 adrenoceptor and it is widely used in critically ill patients (at 1-1.5 µg/kg/h) owing to its sedative effects without respiratory inhibition (25,26). Numerous studies have also reported the anti-inflammatory effects of Dex by reducing the expression of inflammatory factors in certain specific cases (27)(28)(29). Considering previous literature reports and clinical dose analysis (11,12), two doses of dex were examined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…dex has a high affinity for α2 adrenoceptor and it is widely used in critically ill patients (at 1-1.5 µg/kg/h) owing to its sedative effects without respiratory inhibition (25,26). Numerous studies have also reported the anti-inflammatory effects of Dex by reducing the expression of inflammatory factors in certain specific cases (27)(28)(29). Considering previous literature reports and clinical dose analysis (11,12), two doses of dex were examined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, guanabenz has a greater affinity for 2-ARs than NE (ref again). Inflammatory cytokine production by microglia, astrocytes and invading immune cells is suppressed by 2-AR agonists (Figure 3C) [63]. Furthermore, as well as modulating neurotransmission, guanabenz's immunomodulatory effects are highlighted by its systemic action on TLR signaling in mouse dendritic cells [64] and down-regulation of GM-CSF, IL-6, TNF, and IL-1 production in mouse macrophages [65].…”
Section: Can the Enhanced Neuroinflammation Due To Noradrenergic Signaling Inhibition Explain The Behavioral Changes Induced By T Gondii mentioning
confidence: 98%
“…"Beta blockers" are well known β-AR antagonists used systemically to reduce blood pressure that bind ARs in the heart and vasculature [72]. Agonists of the 2-AR, including guanabenz, exhibit a higher affinity for these receptors than NE and act to mimic the action of NE [62,63].…”
Section: Box 2 Noradrenergic Signaling and The Cns Immune Responsementioning
confidence: 99%
“…Dexmedetomidine, a mainly selective adrenergic α2 receptor agonist, has been widely used in pediatric clinical practice for sedation ( Mahmoud et al, 2020 ). It has been reported that dexmedetomidine (DEX) displays an anti-neuroinflammatory and neuroprotective property, possibly through the inhibition of microglial activation and microglial polarization toward the M1 phenotype ( Yeh et al, 2018 ; Gao et al, 2019 ). Moreover, DEX can induce M2 microglial polarization and increase levels of microglia-associated anti-inflammatory cytokines ( Sun et al, 2018 ; Gao et al, 2019 ; Qiu et al, 2020 ), which may also implicate its anti-inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that dexmedetomidine (DEX) displays an anti-neuroinflammatory and neuroprotective property, possibly through the inhibition of microglial activation and microglial polarization toward the M1 phenotype ( Yeh et al, 2018 ; Gao et al, 2019 ). Moreover, DEX can induce M2 microglial polarization and increase levels of microglia-associated anti-inflammatory cytokines ( Sun et al, 2018 ; Gao et al, 2019 ; Qiu et al, 2020 ), which may also implicate its anti-inflammatory effect. Nevertheless, it remains unclear whether DEX can attenuate inflammation and hyperalgesia triggered by systemic LPS injection during the neonatal period.…”
Section: Introductionmentioning
confidence: 99%